Anatomical Proposal for Botulinum Neurotoxin Injection for Glabellar Frown Lines - Yi, Kyu-Ho; Lee, Ji-Hyun; Hu, Hye-Won; Kim, Hee-Jin (Toxins, 2022)
Botulinum neurotoxin injection for treating glabellar frown lines is a commonly used method; however, side effects, such as ptosis and samurai eyebrow, have been reported due to a lack of comprehensive anatomical knowledge. The anatomical factors important for the injection of the botulinum neurotoxin into the corrugator supercilii muscle has been reviewed in this study. Current understanding on the localization of the botulinum neurotoxin injection point from newer anatomy examination was evaluated. We observed that for the glabellar-frown-line-related muscles, the injection point could be more accurately demarcated. We propose the injection method and the best possible injection sites for the corrugator supercilii muscle. We propose the optimal injection sites using external anatomical landmarks for the frequently injected muscles of the face to accelerate effective glabellar frown line removal. Moreover, these instructions would support a more accurate procedure without adverse events.